Design of a novel magnetorheological damper with internal pressure control (Fracture and Structural Integrity, 2015)
In this work we designed and manufactured a novel magnetorheological (MR) fluid damper with internal pressure control. Previous authors’ works showed that the yield stress ?B of MR fluids depends both on the magnetic field intensity and on the working pressure. Since the increase of the magnetic field intensity is limited by considerations like power consumption and magnetic saturation, an active pressure control leads to a simple and efficient enhancement of the performances of these systems. There are three main design topics covered in this paper about the MR damper design. First, the design of the magnetic circuit; second the design of the hydraulic system and third the development of an innovative pressure control apparatus. The design approach adopted is mainly analytical and provides the equations needed for system design, taking into account the desired force and stroke as well as the maximum external dimensions.
Keywords: Magnetorheological damper